Optimizing the management of psoriasis in patients with skin of color: A Canadian Delphi consensusCapsule Summary - Geeta Yadav, MD; Yvette Miller-Monthrope, MD; Jaggi Rao, MD; David N. Adam, MD; Rachel N. Asiniwasis, MD; Parbeer Grewal, MD; Christina Han, MD; Marissa Joseph, MD; Richard G. Langley, MD; Charles W. Lynde, MD; Andrei Metelitsa, MD; Loukia Mitsos, MD, PhD; et al. (JAAD International)
Background: There is limited evidence on treating psoriasis patients with skin of color (SOC), contributing to disparities in accessing appropriate care for these patients. Objectives: This study aimed to develop consensus statements defining SOC terminology and addressing needs to optimize the clinical management of psoriasis in patients with SOC. Methods: Using the modified Delphi methodology 16 Canadian dermatologists with expertise in psoriasis developed consensus statements. Four core faculty members drove the content of the study, and 12 additional panel members were consulted to vote and provide consensus on the content produced by the core faculty. At a final meeting, the full panel revised and voted on the final consensus statements. Results: The exercise resulted in 11 consensus statements on SOC terminology, as well as 5 primary and 4 secondary statements on clinical presentation and differential diagnosis, and treatment guidelines based on evidence and expert opinion. Four additional consensus statements on current assessment tools and access to care were developed based solely on expert opinion. Limitations: The available evidence was limited, low quality, and inappropriate for formal quality assessment. Conclusions: The consensus statements developed in this study may provide valuable guidance to the dermatology community treating psoriasis patients with SOC.